2010
DOI: 10.1016/j.bone.2010.01.382
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for pleiotropic factors in genetics of the musculoskeletal system

Abstract: There are both theoretical and empirical underpinnings that provide evidence that the musculoskeletal system develops, functions, and ages as a whole. Thus, the risk of osteoporotic fracture can be viewed as a function of loading conditions and the ability of the bone to withstand the load. Both bone loss (osteoporosis) and muscle wasting (sarcopenia) are the two sides of the same coin, an involution of the musculoskeletal system. Skeletal loads are dominated by muscle action; both bone and muscle share enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 191 publications
(213 reference statements)
3
68
0
7
Order By: Relevance
“…In previous bone remodeling studies, a rather big 'lazy zone' was required to achieve more realistic results (Huiskes et al 1992), which is also in agreement with the high inhomogeneity we found in our study. Finally, it is possible that genetic or other factors play an important role when the bone structure develops and that bone in fact is only partially optimized for loading conditions (Jepsen 2009;Karasik and Kiel 2010). For example, if bone growth also takes place in the absence of loading, only part of the structure will be load adapted.…”
Section: Discussionmentioning
confidence: 99%
“…In previous bone remodeling studies, a rather big 'lazy zone' was required to achieve more realistic results (Huiskes et al 1992), which is also in agreement with the high inhomogeneity we found in our study. Finally, it is possible that genetic or other factors play an important role when the bone structure develops and that bone in fact is only partially optimized for loading conditions (Jepsen 2009;Karasik and Kiel 2010). For example, if bone growth also takes place in the absence of loading, only part of the structure will be load adapted.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from ethnicity, a second possible confounder is represented by the existence of numerous genes shown to influence both HDLc and BMD through a pleiotropic effect (eg ABCG8, APOE, ESR1) (31). The results, in the subgroup analysis, if replicated in a larger study, would also suggest that statins protect patients with no history of previous fractures (P<0.001, r 2 =0.94).…”
Section: Discussionmentioning
confidence: 93%
“…The 13% lower lean mass in the lower extremities of the amphetamine users is in accordance with the reduced muscular strength that was observed. Loss of lean mass is usually caused by low levels of muscle activity, which has been advocated as an essential cause of age-related bone loss [41,42]. Muscle activity is mainly known to affect bone metabolism by causing mechanical strain [43].…”
Section: Discussionmentioning
confidence: 99%